(untitled) (Orfeu, 2018)
This study discusses the so-called Afro-Peruvian “renascence” period of the 1950s by analyzing the data collected from field research and a case study, thus expanding further discussions on the conflict of production control and circulation of Afro-Peruvian discourse. When speaking of Afro-Peruvian music, both the researchers and the black families sought an historical vindication that compensates for the damage caused by slavocracy and subsequent marginalization. However, this demand proves to be more interested in a political debate that overestimates aesthetical issues, thus disregarding social improvements of the Afro-Peruvian.